2019
DOI: 10.1038/s41598-018-37203-4
|View full text |Cite
|
Sign up to set email alerts
|

Third Trimester Cerebellar Metabolite Concentrations are Decreased in Very Premature Infants with Structural Brain Injury

Abstract: Advanced neuroimaging techniques have improved our understanding of microstructural changes in the preterm supratentorial brain as well as the cerebellum and its association with impaired neurodevelopmental outcomes. However, the metabolic interrogation of the developing cerebellum during the early postnatal period after preterm birth remains largely unknown. Our study investigates the relationship between cerebellar neurometabolites measured by proton magnetic spectroscopy (1H-MRS) in preterm infants with adv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“…Despite the prevalence of cerebellar injury in preterm born infants (Basu et al, 2019;Bouyssi-Kobar et al, 2016;Brossard-Racine et al, 2015;Limperopoulos et al, 2007;Wu et al, 2020) and the links between these insults and poor functional outcomes (Shany et al, 2016;Tran et al, 2017) Systemic inflammation in the fetal and neonatal period plays a key role in disturbance of brain development as shown clinically (Leviton et al, 2016(Leviton et al, , 2018Patra et al, 2017) and supported by preclinical models (Du et al, 2011;Favrais et al, 2011;Gussenhoven et al, 2018) (reviewed in Fleiss et al, 2015Strunk et al, 2014). Prior studies in our validated mouse model of inflammation-associated EoP provide evidence for disruption of white matter integrity in the cerebrum, characterized by elevated fractional anisotropy as measured by DTI (Favrais et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Despite the prevalence of cerebellar injury in preterm born infants (Basu et al, 2019;Bouyssi-Kobar et al, 2016;Brossard-Racine et al, 2015;Limperopoulos et al, 2007;Wu et al, 2020) and the links between these insults and poor functional outcomes (Shany et al, 2016;Tran et al, 2017) Systemic inflammation in the fetal and neonatal period plays a key role in disturbance of brain development as shown clinically (Leviton et al, 2016(Leviton et al, , 2018Patra et al, 2017) and supported by preclinical models (Du et al, 2011;Favrais et al, 2011;Gussenhoven et al, 2018) (reviewed in Fleiss et al, 2015Strunk et al, 2014). Prior studies in our validated mouse model of inflammation-associated EoP provide evidence for disruption of white matter integrity in the cerebrum, characterized by elevated fractional anisotropy as measured by DTI (Favrais et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The precise impact of early exposure to the extra-uterine environment on neurodevelopmental outcomes ( Blencowe et al, 2013 ) in children born premature has yet to be fully explored. However, recent studies using advanced brain imaging techniques have shown altered metabolic profiles ( Ball et al, 2013a , 2013b ; Basu et al, 2019 ; Kwon et al, 2014 ; Vinall et al, 2013 ), cortical surface changes ( Ajayi-Obe et al, 2000 ; Boardman et al, 2007 ; Lefèvre et al, 2016 ; Orasanu et al, 2016 ), and impaired brain growth ( Padilla et al, 2015 ) in prematurely born infants. Cerebral and cerebellar growth trajectories in third trimester preterm infants without brain injury also lagged behind healthy in utero fetuses ( Bouyssi-Kobar et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Despite the prevalence of cerebellar injury in preterm born infants 5, 6, 24, 75, 76 and the links between these insults and poor outcomes in preterm born infants 77, 78 , there is not many studies focused on the cerebellum in models of preterm brain injury. We have addressed this issue and we have documented by MRI that in our model of inflammation-associated encephalopathy of prematurity that there is a global change in absolute volumes of the mouse brain, with a specific loss of cerebellar volume into adulthood.…”
Section: Discussionmentioning
confidence: 99%